Phosphate-Dependent Regulation of Growth and Stresses Management in Plants - Bechtaoui, Noura; Rabiu, Muhammad Kabir; Raklami, Anas; Oufdou, Khalid; Hafidi, Mohamed; Jemo, Martin (Frontiers in Plant Science, 2021)
The importance of phosphorus (P) in the regulation of plant growth function is well studied. However, the role of the Pi molecule in the mitigation of abiotic stresses such as drought, salinity, heavy metal, heat, and acid stresses are poorly understood. We revisited peer-reviewed articles on plant growth characteristics that are P-dependently regulated under the sufficient-P and low/no-P starvation alone or either combined with one of the above-mentioned stress. We found that the photosynthesis rate, stomatal conductance decreased under phosphate (Pi)-starved conditions. The total chlorophyll contents increased in the P-deficient plants, owing to the lack of Pi molecules to sustain the photosynthesis functioning, particularly the Rubisco and fructose-1,6-bisphosphatase function. The dry biomass of shoots, roots and P concentrations significantly reduced under Pi starvation with marketable effects in the cereal than in the legumes. To mitigate P stress, plants activate alternative regulatory pathways, the Pi-dependent glycolysis and mitochondrial respiration in the cytoplasm. Plants grown under well-Pi supplementation of drought stress exhibited higher dry biomass of shoots than the no-P treated ones. The Pi supply to plants grown under heavy metals stress reduced the metal concentrations in the leaves for the cadmium, and lead, but could not prevent them from absorbing heavy metals from soils. To detoxify from heavy metal stress, plants enhance the catalase and ascorbate peroxidase activity that prevents lipid peroxidation in the leaves. The HvPIP and PHO1 genes were over-expressed under both Pi starvation alone, and Pi plus drought, or Pi plus salinity stress combination, implying their key roles to mediate the stress mitigations. Agronomy Pi-based interventions to increase Pi at the on-farm levels are discussed. Revisiting the roles of P in growth and its better management in agricultural lands or where P is supplemented as fertilizer could help the plants to survive under abiotic stresses.